Therapeutic Potential of Secretome-Derived Wharton's Jelly Mesenchymal Stem Cells in Psoriasis Vulgaris: A Case Study - Azzahara, Salma Yasmine; Agustina, Rita; Prawitasari, Salindri (Stem Cell and Cancer Research (SCCR), 2023)
Background: Psoriasis is a chronic, immune-mediated skin disease that also has systemic manifestations. Case: In this report, we discuss our findings about a 47-years old psoriasis suffering male patient with a Psoriasis Area Severity Index (PASI) score of 10.8, treated with Wharton’s Jelly Mesenchymal Stem Cells-derived Secretome (S-MSCs). Remarkably, complete regression was recorded within a treatment period of a week only. Result: The patient demonstrated a decrease in PASI, from 10.8 to 3.2 after 1 infusion and followed by 4 intramuscular injections of S-MSCs. Bioactive factors secreted by MSCs, cytokines and growth factors, are very likely to be the principal molecules which play a vital role in inflammatory modulation and skin tissue regeneration. No serious adverse events were noted for the patient as a result of secretome infusion and intramuscular injection. Conclusion: This report demonstrates safety and promises to be an effective strategy using S-MSCs treatment for managing the psoriatic issue and, thus, may offer as an alternative approach to overcome the limitations of the cell-based therapy.